2014
DOI: 10.1371/journal.pone.0107287
|View full text |Cite
|
Sign up to set email alerts
|

On Three-Dimensional Flow and Heat Transfer over a Non-Linearly Stretching Sheet: Analytical and Numerical Solutions

Abstract: This article studies the viscous flow and heat transfer over a plane horizontal surface stretched non-linearly in two lateral directions. Appropriate wall conditions characterizing the non-linear variation in the velocity and temperature of the sheet are employed for the first time. A new set of similarity variables is introduced to reduce the boundary layer equations into self-similar forms. The velocity and temperature distributions are determined by two methods, namely (i) optimal homotopy analysis method (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(42 citation statements)
references
References 40 publications
4
38
0
Order By: Relevance
“…In such situations, it is better to tackle the models numerically. Therefore, for the purpose of solving the models under consideration (γAl 2 O 3 -H 2 O and γAl 2 O 3 -C 2 H 6 O 2 ), a reliable numerical algorithm referred to as Runge-Kutta (RK) with the addition of the shooting technique ( [14,15]) is adopted. For this, the fourth-order RK technique is selected.…”
Section: Mathematical Analysismentioning
confidence: 99%
“…In such situations, it is better to tackle the models numerically. Therefore, for the purpose of solving the models under consideration (γAl 2 O 3 -H 2 O and γAl 2 O 3 -C 2 H 6 O 2 ), a reliable numerical algorithm referred to as Runge-Kutta (RK) with the addition of the shooting technique ( [14,15]) is adopted. For this, the fourth-order RK technique is selected.…”
Section: Mathematical Analysismentioning
confidence: 99%
“…for the above streamfunctions given in (5). Plugging the ansatz defined in (5) and (6) in the momentum boundary-layer equations (3), we get the coupled nonlinear ordinary differential equations as…”
Section: Flow Theorymentioning
confidence: 99%
“…In addition, with m =0, the Blasius boundary layer has a 3‐dimensional cousin . In this line of study, Khan et al have investigated 3‐dimensional boundary‐layer flow in a still fluid in which the wedge movement has the above forms in both directions and have shown that for positive values of m (in our notation), the thickness of the boundary layer decreases. The boundary layer forms because of the flow of a viscous fluid over the 2‐ to 3‐dimensional stretching and shrinking porous deforming bodies and the longitudinal fins in rectangular duct (Turkyilmazoglu), and the flow model includes both heat transfer and magnetic effect (Turkyilmazoglu).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Some recent studies of boundary layer flow in presence of a magnetic field include those of Mabood and his group [1921]. For the case of a nonlinearly stretching sheet, we note the work of Khan et al [22]. …”
Section: Introductionmentioning
confidence: 99%